Nutritional and Anti Oxidant Potential of Commonly Growing Plant Foods from Southern India - Rajendran, C.; KirtanaKirtana, S.; Venkatesh, Rashmi; Yadav, Pooja; Raghavan, Anilakumar Kandankath (Defence Life Science Journal, 2020)
Certain varieties of plants are abundantly available with rich in nutrients, but the complete sets of nutritional composition studies have not been carried out. Among them, the matured leaves of Murrya keonigii; seeds and leaves of Moringa oleifera, and fruit pulp of Aegle marmelos were chosen. The proximate analysed for above samples showed that the moisture varies from 2.4% -8.2%, crude proteins from 18.75%- 34.57 %, fat content from 5.6% -19.6%, ash content from 3.87%-15.6% and carbohydrate from 28.65% - 41.23%, respectively. Estimation of mineral contents revealed that the leaves and seeds of moringa had higher concentrations than others. Determination of total antioxidant (total flavonoid) was higher (63.550 μg (RU)/ml of samples) in matured curry leaves than others. Determination of in vitro antioxidant activity with FRAP revealed highest activity in curry leaves (174.5μg) to a least activity with seeds of moringa (45.725 μg), whereas the DPPH revealed highest activity for fruit pulp of bael (1680.6μg ascorbic acid) to the least in leaves of moringa (263.15 μg ascorbic acid equivalent/mg). The ABTS showed IC50 value of 210.52 ±0.5774 for curry leaf, 487.8 ±0.3347 and 205.36 moringa seeds and leaves and 513.24 IC50 μg for pulp of bael fruit. Quantitative analysis of water soluble vitamins such as thiamine (B1) varied from 2.172 -5.558 mg; riboflavin (B2) from 2.201 -11.354 mg; pyridoxine (B6) from 4.608 -194.001 mg; biotin (B7) from 36.864 -153.027 mg, respectively. Further, the vitamin C (ascorbic acid) varied from 6.733 -23.142 mg /100g of oven dried samples, respectively. Therefore, the above foods are well intended to be included in routine diet regime and may also be willing to utilise for food supplementation with other suitable diets to manage the conditions such as malnutrition and nutrient deficiencies.